Measurement properties of patient-reported outcome measures of mental help-seeking attitude: a systematic review of psychometric properties - Bian, Cheng; Chen, Shu-Yan; Yan, Shi-Rui; Zhao, Wei-Wei; Wang, Ru-Xuan; Cheng, Yin; Zhang, Yan-Hong (Frontiers in Psychiatry, 2023)
Background: At present, the phenomenon of patients with mental disorders not seeking mental help is very serious, and the mental help-seeking attitude is the central structure of the help process. However, there is no consensus on which patient-reported outcome measure (PROM) should be used to assess mental help-seeking attitudes. Objective: The systematic review aims to critically appraise, compare, and summarize the measurement quality of the all-available PROMs about mental help-seeking attitudes to provide evidence-based guidance and reference for clinical researchers. Methods: A systematic search was conducted in 9 databases (PubMed, Embase, Web of Science, Medline, APA, CINAHL, Sinomed, CNKI, and WanFang) since the establishment of the database until November 30, 2022 to identify articles on the PROMs of mental help-seeking attitudes. We used the COSMIN guidelines to evaluate the methodological quality and measurement properties of all-available PROMs, and a modified Grading, Recommendation, Assessment, Development, and Evaluation (GRADE) system to evaluate the level of evidence supporting each rating. Finally, the recommendation level is given according to the overall quality of each PROM. Results: We identified 29 studies representing 13 PROMs out of 2828 screening studies. The overall quality of the included PROMs varied, with 6 rated as class B, 6 as class C, and only the Mental Help Seeking Attitudes Scale (MHSAS) as class A. Conclusion: The measurement characteristics of MHSAS have been the most comprehensive evaluation, and it has good reliability and validity, and high feasibility for clinical application, so it can be temporarily recommended for use, but the above conclusions still need to be supported by more high-quality evidence.